El Reglamento Interno de Trabajo como fuente de Derecho: importancia y visión jurisprudencial - Ulloa Millares, Daniel Augusto (2016)
The Internal Labor Regulations is a rule law that could be created by the employer. In that sense, its position in the system of sources is residual because it can not contravene the government rules nor the collective agreement content. However, case law has considered it many times to assess the validity of a dismissal or the existence of an employment relationship. This article seeks to review these issues and to assess the validity of the rule that regulates it (Supreme Decree 39-91-TR).